2010
DOI: 10.3858/emm.2010.42.11.078
|View full text |Cite
|
Sign up to set email alerts
|

Genistein activates endothelial nitric oxide synthase in broiler pulmonary arterial endothelial cells by an Akt-dependent mechanism

Abstract: Deregulation of endothelial nitric oxide synthase (eNOS) plays an important role in the development of multiple cardiovascular diseases. Our recent study demonstrated that genistein supplementation attenuates pulmonary arterial hypertension in broilers by restoration of endothelial function. In this study, we investigated the molecular mechanism by using broiler pulmonary arterial endothelial cells (PAECs). Our results showed that genistein stimulated a rapid phosphorylation of eNOS at Ser 1179 which was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The studies of Tan had found that ET‐1 increased the expression of MMP‐2 and contributes to pulmonary vascular remodelling, and speculated increased vascular MMP‐2 might amplify its own expression through increased ET‐1 activity (Tan et al., ; ). Our results agree with previous reports on the phytoestrogen (Yang et al., ; Hassanpour et al., ). And, our findings indicate that Trifolium pratense isoflavone dietary treatment reduces ET‐1 levels in lungs and regulates the secretion of NO and ET‐1, thereby leading to a reduction of PAH.…”
Section: Discussionsupporting
confidence: 94%
“…The studies of Tan had found that ET‐1 increased the expression of MMP‐2 and contributes to pulmonary vascular remodelling, and speculated increased vascular MMP‐2 might amplify its own expression through increased ET‐1 activity (Tan et al., ; ). Our results agree with previous reports on the phytoestrogen (Yang et al., ; Hassanpour et al., ). And, our findings indicate that Trifolium pratense isoflavone dietary treatment reduces ET‐1 levels in lungs and regulates the secretion of NO and ET‐1, thereby leading to a reduction of PAH.…”
Section: Discussionsupporting
confidence: 94%
“…We found that Gen restored levels of cGMP and p-eNOS at Ser 1177 and p-Akt at Ser 473 in hypoxic lungs and pulmonary arteries. The protein kinase Akt has been proposed to phosphorylate eNOS at Ser 1177 and to increase eNOS activity in response to various stimuli in vascular endothelial cells (7), whereas Gen activated eNOS through a PI3K/Akt-dependent mechanism in pulmonary arterial endothelial cells (45). For the first time, however, the present study of HL rats demonstrated that Gen treatment upregulated the PI3K/Akt pathway in the lungs and pulmonary arteries.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, it has been shown to reverse in vitro the loss of T-cell signaling components at post-menopausal estrogen levels, with no significant effect at pre-menopausal estrogen levels [92]. In broiler pulmonary arterial endothelial cells genistein stimulated a rapid phosphorylation of eNOS activating the eNOS/NO axis; the activation of eNOS was not mediated through estrogen receptors or tyrosine kinase inhibition, but via a phosphatidylinositol 3-kinase (PI3K)/Aktdependent signaling pathway, as the eNOS activity and related NO release were largely abolished by pharmacological inhibitors of PI3K or Akt [93].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%